Consumption of bushmeat around a major mine, and matched communities, in Madagascar. (June 2015) - Randriamamonjy, Voahirana C.; Keane, Aidan; Razafimanahaka, H. Julie; Jenkins, Richard K.B.; Jones, Julia P.G.
Abstract: Mining can have serious biodiversity consequences and many mining operations take steps to mitigate their impacts. Evaluating their success poses a significant challenge because appropriate counterfactuals (what would have happened in the absence of the mine) are often unavailable. We aimed to estimate the effects of education and enforcement measures carried out by a large mine in eastern Madagascar on local consumption of illegal bushmeat. We adopt a quasi-experimental approach and use an interview technique designed to reduce sensitivity biases to compare levels of consumption amongst mine employees and people living within the mine's intervention area with those of statistically matched control groups, and to relate differences to respondents' knowledge of relevant wildlife laws. Consumption was lower, and awareness of the law higher, amongst mine employees and those living in the mine's intervention area. However caution should be applied in interpreting these results as evidence of the effectiveness of anti-bushmeat efforts by the mine due to potential confounding factors: for example abundance of bushmeat species may vary between the study areas, and our method may not have completely removed the sensitivity of questions about illegal consumption. This illustrates the challenges of evaluating conservation impacts. We highlight the low level of understanding of wildlife laws, including among mine employees, and suggest better communication of these laws, as part of an education programme, could be a useful first step towards reducing illegal hunting.